The Influence of Market Orientation and Entrepreneurial Orientation on Marketing Performance: Organizational Agility as a Mediator - Luthvi Rachman Er; Aloysius Harry Mukti (International Journal of Science and Society, 2023)
This study aims to determine the impact of market orientation and entrepreneurial orientation on marketing performance mediated by organizational ambidexterity. The unit analysis for this study is employees who work at Bina Insani University, located in Bekasi City, West Java Province. This research uses quantitative methods. The population of this study were 100 Bina Insani University employees. Total respondents are 100 respondents. Data were collected through questionnaires through the census method. Data were analysed using Partial Least Square. This study confirms that market orientation does not influence marketing performance significantly. However, it confirmed the direct impact of positive and significant entrepreneurial orientation on marketing performance. This study also confirms the role of organizational ambidexterity as a mediator in the relationship between entrepreneurial orientation and marketing performance but not in the relationship between market orientation and marketing performance. Thus, Bina Insani University needs to always improve the implementation of its entrepreneurial orientation and organizational ambidexterity to ensure the improvement of its marketing performance.